The mechanism of the effects of Monascus jmbA rice on increased platelet count in Wistar rats infected with Dengue virus serotype 3 - Erwin Astha Triyono (MDPI AG, 2020)
Background: Several traditional medicines have been developed among communities as part of the efforts to improve thrombocytopenia in patients with Dengue virus infection (DVI). Among those efforts is the administration of Monascus jmbA rice (MJR), which is rice fermented with Monascus purpureus. The administration of MJR is believed to increase the platelet count in patients with DVI. Aim: The objective of this study is to elucidate the mechanism of the effects of MJR on increased levels of platelets in DVI serotype 3 through changes in IL-3, IL-6, IL-11 and TNF-α. Methods: It was a true experimental laboratory study using the randomized post-test only control group design. The study compared between groups of wistar rats were being treated only with group IVD wistar rats who experienced treatment followed by administration of MJR as well as groups of wistar rats without any treatment as a control group. Results: The increase in platelet count in the group treated with DVI + MJR was higher than that treated with only DVI and the difference was a significant (P<0.05). Increased levels of TNF-α in the group treated with DVI + MJR were lower than that treated with only DVI and the difference was significant (P<0.05). The significant levels of the causal relationship of TNF-α with IL-6, TNF-α with IL-11 and IL-6 with platelets were 0.044 (P<0.05), 0.029 (P<0.05) and 0.041 (P<0.05), respectively. Conclusion: MJR is capable of increasing platelet count through the role of TNF-α and IL-6 in Wistar rats infected with DVI serotype 3.